Lignin composition is more important than content for maize stem cell wall degradation. (25th September 2017) - He, Yuan; Mouthier, Thibaut MB; Kabel, Mirjam A; Dijkstra, Jan; Hendriks, Wouter H; Struik, Paul C; Cone, John W
Abstract: BACKGROUND: The relationship between the chemical and molecular properties – in particular the (acid detergent) lignin (ADL) content and composition expressed as the ratio between syringyl and guaiacyl compounds (S:G ratio) – of maize stems and in vitro gas production was studied in order to determine which is more important in the degradability of maize stem cell walls in the rumen of ruminants. Different internodes from two contrasting maize cultivars (Ambrosini and Aastar) were harvested during the growing season. RESULTS: The ADL content decreased with greater internode number within the stem, whereas the ADL content fluctuated during the season for both cultivars. The S:G ratio was lower in younger tissue (greater internode number or earlier harvest date) in both cultivars. For the gas produced between 3 and 20 h, representing the fermentation of cell walls in rumen fluid, a stronger correlation ( R 2 = 0.80) was found with the S:G ratio than with the ADL content ( R 2 = 0.68). The relationship between ADL content or S:G ratio and 72‐h gas production, representing total organic matter degradation, was weaker than that with gas produced between 3 and 20 h. CONCLUSION: The S:G ratio plays a more dominant role than ADL content in maize stem cell wall degradation. © 2017 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.